1996
DOI: 10.1046/j.1365-2567.1996.d01-714.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th1 and Th2 cells in anterior chamber‐associated immune deviation

Abstract: SUMMARYThe immunological privilege of the anterior chamber (AC) of the eye is due, at least in part, to a selective antigen-specific down-regulation of delayed-type hypersensitivity (DTH) and a normal induction of antibody responses: a phenomenon that has been termed anterior chamber-associated immune deviation (ACAID). This dichotomy in the systemic immune responses is suggestive of a Thelper type-2 (Th2)-dominated immune phenotype in which a Th2 cell population is preferentially activated and cross-regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…However, the suppression of IgG and IgM Ab responses in that study was due to IFN-␥ produced by Qa-1-restricted CD8 ϩ regulatory T cells (10). By contrast, ACAID involves the down-regulation of IFN-␥ and a concomitant induction of IL-10 production (31)(32)(33). In other systems, Qa-1-restricted CD8 ϩ regulatory T cells have been shown to down-regulate Th1 immune responses and mitigate Th1-mediated autoimmune diseases, such as experimental allergic encephalomyelitis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the suppression of IgG and IgM Ab responses in that study was due to IFN-␥ produced by Qa-1-restricted CD8 ϩ regulatory T cells (10). By contrast, ACAID involves the down-regulation of IFN-␥ and a concomitant induction of IL-10 production (31)(32)(33). In other systems, Qa-1-restricted CD8 ϩ regulatory T cells have been shown to down-regulate Th1 immune responses and mitigate Th1-mediated autoimmune diseases, such as experimental allergic encephalomyelitis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the immune response following intraocular injection of AAV is similar to that described in ACAID (ie, a predominant Th2 like response). [25][26][27]55 One question relating to the AAV-induced humoral response is whether it would be possible to readminister the virus/transgene in the presence of virus-specific antibodies. Studies in mice and in monkeys have demonstrated that these antibodies are not neutralizing and that it is possible to obtain additional transduction events.…”
Section: Immune Response To Intraocular Delivery Of Viral Vectors J Bmentioning
confidence: 99%
“…We reason this difference may be the case from previous reports examining the immunosuppressive environment of the anterior ocular chamber. Under homeostatic conditions, the anterior chamber of the eye has a specific deficiency of Ag-specific delayed-type hypersensitivity (DTH)-mediating T cells, mediated by Th1 cells, and a shift toward a Th2 phenotype of CD4 ϩ T cells (74). This situation would therefore be different from the normal immune environment in the TG, potentially explaining some of the differences observed in the effect of Ad:IFN-␥ in cornea vs TG.…”
Section: Discussionmentioning
confidence: 99%